2003
DOI: 10.1095/biolreprod.102.009035
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Progesterone Receptor (PR) A and B Isoforms in Mouse Granulosa Cells: Stage-Dependent PR-Mediated Regulation of Apoptosis and Cell Proliferation1

Abstract: The intracellular progesterone receptor (PR) in the mammalian ovary is a part of the physiological pathway that facilitates ovulation. Two PR isoforms (A and B) exist, with different molecular and biological functions. Previous studies have revealed that the cellular ratio of the PR isoforms is important for progesterone-responsive tissues and is under developmental control in different species. However, the relative expression of PR isoforms in the ovary is unknown. In this study we have demonstrated first th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
77
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 45 publications
9
77
0
2
Order By: Relevance
“…However, the regulation of PR proteins has been found to be tissue and cell type specific in female reproductive tissues in vivo (20). Our laboratory has demonstrated that treatment with human chorionic gonadotropin (hCG), mimicking endogenous preovulatory luteinizing hormone surge, induces the levels of PR protein isoforms in periovulatory granulosa cells in mouse ovary (62). Similar observations have been made in ovaries from intact adult mice during the estrous cycle (19) and in humans (22).…”
mentioning
confidence: 59%
“…However, the regulation of PR proteins has been found to be tissue and cell type specific in female reproductive tissues in vivo (20). Our laboratory has demonstrated that treatment with human chorionic gonadotropin (hCG), mimicking endogenous preovulatory luteinizing hormone surge, induces the levels of PR protein isoforms in periovulatory granulosa cells in mouse ovary (62). Similar observations have been made in ovaries from intact adult mice during the estrous cycle (19) and in humans (22).…”
mentioning
confidence: 59%
“…There is some confusion about the relative amounts of each in the corpus luteum. In mice, some authors have found that granulosa cell PR A is higher than PR B but PR is lost during luteinisation (Shao et al 2003), and others have found PR B to be predominant in the granulosa cell and present in the corpus luteum (Gava et al 2004). In the primate corpus luteum, Western blotting suggested that the major PR variant is the B isoform .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these candidates were reported in other species and/or contexts as potential markers of competence, e.g. TNFAIP6 in mouse, porcine CCs (Fulop et al 2003, Nagyova et al 2009), HAS2 in human cumulus GCs (McKenzie et al 2004), PGR in mouse GCs (Shao et al 2003), and INHBA in bovine GCs (Fayad et al 2004).…”
Section: Potential In Vivo Markers Of Oocyte Competencementioning
confidence: 99%